Progress of clinical research on targeted therapy combined with thoracic radiotherapy for non-small-cell lung cancer - Zhuang HQ; Zhao XZ; Zhao LJ; Chang JY; Wang P (Dove Medical Press, 2014)
Hongqing Zhuang,1,* Xianzhi Zhao,1,* Lujun Zhao,1 Joe Y Chang,2 Ping Wang1 1Department of Radiotherapy, Tianjin Medical University Cancer Institute and Hospital, National Clinical Research Center for Cancer, Tianjin Key Laboratory of Cancer Prevention and Therapy, and Tianjin Lung Cancer Center, Tianjin, People's Republic of China; 2Department of Radiation Oncology, Division of Radiation Oncology, The University of Texas MD Anderson Cancer Center, Houston, TX, USA *These authors contributed equally to this paper Abstract: The combination of radiotherapy and targeted therapy is an important approach in the application of targeted therapy in clinical practice, and represents an important opportunity for the development of radiotherapy itself. Numerous agents, including epidermal growth factor receptor, monoclonal antibodies, tyrosine kinase inhibitors, and antiangiogenic therapies, have been used for targeted therapy. A number of studies of radiotherapy combined with targeted therapy in non-small-cell lung carcinoma have been completed or are ongoing. This paper briefly summarizes the drugs involved and the important related clinical research, and indicates that considerable progress has been made with the joint efforts of the two disciplines. Many issues, including drug selection, identification of populations most likely to benefit, timing of administration of medication, and side effects of treatment require further investigation. However, further fundamental research and accumulation of clinical data will provide a more comprehensive understanding of these therapies. Targeted therapy in combination with radiotherapy has a bright future. Keywords: non-small-cell lung carcinoma, radiotherapy, epidermal growth factor receptor, monoclonal antibody, tyrosine kinase inhibitors, antiangiogenic therapies